Temporal-Spatial Variations Analysis of Surface Temperature in Kalimantan Region for The Period of 2010 - 2020 - Fitrianingtyas, Rahmawati; Palupi, Indriati Retno (Jurnal Fisika Flux: Jurnal Ilmiah Fisika FMIPA Universitas Lambung Mangkurat, 2024)
Surface temperature information is important to study because it affects other climate parameters and has an impact on various sectors. This study aims to analyze the temporal and spatial variations of maximum surface temperature on Kalimantan Region during the period 2010 to 2020. The data used is Surface Maximum Temperature (SMT) in the form of a 0.5o x 0.5o grid from the Climate Prediction Center (CPC) NOAA PCL. The results of the temporal analysis showed that the highest monthly SMT values occurred in May (32.00o C) and September (31.75o C). While the lowest monthly SMT values were found in January (30.88o C) and July (31.40o C).  The results of the annual SMT trend analysis show that the surface temperature in the Kalimantan Region has increased at an average rate of 0.03°C per year. This value is higher than the increase in global surface temperature (~0.02°C per year). Based on the results of spatial analysis, it was known that the distribution of SMT on Kalimantan Region tends to be stable in the range of 25o C to 35o C throughout the year. Spatial analysis of SMT in 2011 showed that low values (25o - 31o C) dominated South Kalimantan Province , while high values (33°C - 35°C) dominated West Kalimantan Province. The results of the 2019 SMT spatial analysis revealed a similar pattern to 2011. However, there was a significant increase in temperature compared to 2011, especially in the high SMT values observed in West Kalimantan and East Kalimantan Provinces.